Diagnostic journey in Spinal Muscular Atrophy: Is it still an odyssey? - Pera, Maria Carmela (PLoS One, 2020)
BACKGROUND: The advent of new therapies has increased the need to achieve early diagnosis in Spinal Muscular Atrophy (SMA). The aim of the present study was to define the age of diagnosis in the three main types of SMA with pediatric-onset and the timing between the recognition of clinical signs and confirmed genetic diagnosis. METHODS: All patients with a confirmed diagnosis of type I, II, III SMA followed in 5 Italian centers were included in this study, assessing age at symptoms onset, presenting sign or symptom, age at diagnosis, interval between clinical onset and diagnosis and type of medical investigations conducted in order to obtain the diagnosis. RESULTS: The cohort included 480 patients, 191 affected by SMA type I, 210 by type II and 79 by type III. The mean age at diagnosis was 4.70 months (SD ±2.82) in type I, 15.6 months (SD±5.88) in type II, and 4.34 years (SD±4.01) in type III. The mean time between symptom onset and diagnosis was 1.94 months (SD±1.84) in type I, 5.28 months (SD±4.68) in type II and 16.8 months (SD±18.72) in type III. CONCLUSIONS: Our results suggest that despite improved care recommendations there is still a marked diagnostic delay, especially in type III. At the time new therapies are becoming available more attention should be devoted to reducing such delay as there is consistent evidence of the benefit of early treatment.